Hilirization of Nori Sawi, Hydroponic Management Training, and Digitalization at Larangan Mega Asri Sidoarjo - Kusnanto, Hadi; Sari, Meirna Dewita; Marina, Nurul Fitria; Saputro, Andre Ridho; Putra, Andhika Cahyono; Syammakh, Isa Ma'ruf (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This community service program was implemented at the Larangan Mega Asri, Sidoarjo with the aim of increasing the economic independence of residents through three main approaches, hilirization of dried nori mustard greens products, hydroponic management training, and social media digitalization training. Method: Method is designed with a participatory approach that actively involves partners from the planning, implementation, to evaluation stages. Practical Applications: The results of the activity show that the community has acquired new skills in processing mustard derivative products, is able to manage the hydroponic system independently, and is more adaptive to the use of social media as a marketing tool. This program is a positive first step in terms of increasing productivity, business diversification, and strengthening the digital marketing network of Larangan Mega Asri. Conclusion: The combination of product hilirization, strengthening hydroponic cultivation, and marketing digitalization has created a synergy that encourages the community-based creative economic ecosystem.